Is the Accreditation of an Arbitrary Dismissal Sufficient to result in the Payment of Compensation for Moral Damages? - Colona Ortega, José Carlos (2016)
The author analyzes the rules of civil liability and its application in the workplace to establish the right to compensation as a result of irregular dismissal. In particular, it seeks to determine if a judicial declaration of unfair dismissal is sufficient to justify the payment of compensation for moral damages for the worker element.